Clinical and ultrasonographic findings of a tear of the gastrocnemius muscle and enthesopathy of the origin of the superficial digital flexor muscle in a reining Quarter Horse mare. (5th March 2020) - Romero, J. M.; Pressanto, M. C.; Pepe, M.; Di Meo, A.; Beccati, F.
Summary: Proximal gastrocnemius and superficial digital flexor (SDF) muscle injuries are reported in the horse but are uncommon. In adult horses, the definitive diagnosis is more commonly based on clinical signs with or without the use of radiographic examination and/or nuclear scintigraphy. This case report describes the clinical and ultrasonographic findings of a tear of the gastrocnemius muscle in a 6‐year‐old reining mare. At standing physical examination, there was a sickled hock appearance, with the point of the hock of the left hindlimb lower (dropped hock) than that of the right hindlimb. At dynamic examination at walk, the mare had instability of the left hock characterised by medial rotation of the hoof and lateral rotation of the point of the hock (twisting motion); at trot, the horse showed mild/moderate left hindlimb lameness characterised by more downward movement of the pelvis during weightbearing of the lame limb compared with that of the sound limb. Ultrasonographic examination of the left thigh and crus showed a large irregular hypoechogenic area and irregularly shaped, retracted muscle stumps on the lateral aspect of the gastrocnemius muscles; the proximal insertion of the SDF muscle on the supracondylar fossa of the femur was irregular in its outline, hypoechogenic and thickened compared with that of the right side. Characteristic muscle fibre pattern was not identified in the left gastrocnemius muscle. On the radiography, a mild irregularity of the bone margin of the lateral supracondylar tuberosity was detected on the caudo 45° medial‐craniolateral oblique view of the distal femur. Clinical and diagnostic imaging findings were consistent with partial failure of the caudal part of the reciprocal apparatus and injury of the gastrocnemius and SDF muscles/origin. The horse was managed conservatively by corrective shoeing, muscle relaxing drugs, controlled exercise and manual stretching.